An efficient deep learning approach to detect COVID-19 infected lungs using image data - Kabir, Asif Rezwan; Roy, Shutirtha; Zerin, Nusrat; Afrin, Sheikh Sharia; Choudhury, Anika Jahan (Brac University, 2022)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2022.